Penatalaksanaan dan Pemilihan Teknik Augmentasi Tulang pada Pemasangan Implan Dental - Eureka Koharaudi Halimi; Yessy Ariesanti (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Inadequate bone condition in dental implants can be a fundamental problem. The success of implant therapy depends on adequate bone thickness at the implant site. Inadequate bone condition due to atrophy, periodontal disease, trauma, or vertical, horizontal, and sagittal intermaxillary relationships can result in insufficient bone volume for implant placement. Bone augmentation for implant treatment it’s a common practice to obtain the function and aesthetics expected in areas of inadequate bone. Several techniques and materials of bone augmentation with varying success rates are known, one of which is Guided Bone Regeneration (GBR). Objective: To add information about the management of bone augmentation in dental implants using the Guided Bone Regeneration (GBR) technique. Case Report: A 20-year-old female patient attended a clinic to solve a functional problem and prevent dental shifting after tooth extraction. She wanted to have permanent dentures for the left mandibular. After undergoing several examinations, it was decided to perform dental implants on tooth 36, diameter 3.4 mm and length 10.5 mm with a cemented-screw type PFM crown. In this case, the bone augmentation technique is Guided Bone Regeneration (GBR) with allograft bone grafts. After being observed for approximately one year, it appears that new bone formation has occurred, which supports the success of the dental implant treatment. Conclusion: Various bone augmentation techniques are effective in correcting inadequate bone conditions prior to implant placement.